Adaptation of Pre-Service Teacher form of the Parental Involvement Survey - Nihal Lindberg, E.; Ulker-Tumlu, Gamze (Elsevier BV, 2012)
AbstractTeachers are considered to play a vital role in students’ achievements. However, without parental support, teachers can not provide for all needs of the students. Indeed, Epstein & Becker (1982) stated that the job of teaching could not be accomplished without programs that involve parents. In a study, McBride (1991) nevertheless found that pre-service teachers thought they had little preparation for implementing parental involvement strategies. In this study, the aim was to adapt The Parental Involvement Questionnaire to Turkish. The questionnaire, adapted by McBride (1991), examines the opinions of preservice teachers about parent involvement. This questionnaire was originally developed by Epstein and consists of 82 Likert type scale items, 6 open-ended questions, and 10 demographic questions. Therefore, preservice teachers’ ideas about parental involvement were compiled by means of a questionnaire based on Epstein's framework of five dimensions of parental involvement. The research was conducted with 266 university students from the Educational Faculty of Kastamonu University, Turkey. The confirmatory factor analysis is used to investigate the factor structure of the questionnaire. In addition, Cronbach alfa is used to describe the reliability of the items. The results showed that the survey is appropriate for Turkish university students.
Keywords: pre-service teacher; Parental participation; inventory adaptation; teacher education; 4. Education